2021
DOI: 10.3389/fevo.2021.611362
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential Risk of Rock-Climbing for Cliff Plant Species and Natural Protected Areas of Spain

Abstract: In recent years, the popularity of rock-climbing has grown tremendously, setting an increasing pressure on cliff habitats. Climbing may be particularly harmful in the Mediterranean biome due to its appropriate environmental conditions for climbing. A few studies have identified the effect of climbing on plant diversity at a small-scale (namely locally or even just in specific climbing areas). However, no studies exist assessing the potential risk of rock-climbing on a broad-scale (e.g., regional or national). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Despite these extreme conditions, cliff habitats provide a high diversity of microhabitats, harboring many plant species, often including endemic and endangered species (Larson et al, 2000 ; Lavergne et al, 2003 ). Particularly, Spain has been chosen as a key conservation territory and is one of the most biodiverse countries in the European Union, holding a great diversity of cliff specialist plants with more than 150 being cliffs threatened plant species (deCastro‐Arrazola et al, 2021 ; National Biodiversity Strategy, 2020 ). Moreover, a previous study indicated the need for establishing protection priorities in Spanish cliff habitats but mainly considered as criteria endangered plants and natural protected areas (deCastro‐Arrazola et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these extreme conditions, cliff habitats provide a high diversity of microhabitats, harboring many plant species, often including endemic and endangered species (Larson et al, 2000 ; Lavergne et al, 2003 ). Particularly, Spain has been chosen as a key conservation territory and is one of the most biodiverse countries in the European Union, holding a great diversity of cliff specialist plants with more than 150 being cliffs threatened plant species (deCastro‐Arrazola et al, 2021 ; National Biodiversity Strategy, 2020 ). Moreover, a previous study indicated the need for establishing protection priorities in Spanish cliff habitats but mainly considered as criteria endangered plants and natural protected areas (deCastro‐Arrazola et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Spain has been chosen as a key conservation territory and is one of the most biodiverse countries in the European Union, holding a great diversity of cliff specialist plants with more than 150 being cliffs threatened plant species (deCastro‐Arrazola et al, 2021 ; National Biodiversity Strategy, 2020 ). Moreover, a previous study indicated the need for establishing protection priorities in Spanish cliff habitats but mainly considered as criteria endangered plants and natural protected areas (deCastro‐Arrazola et al, 2021 ). These protected areas are thus meant to protect rare and threatened plant and animal species and serve as fundamental tools for ecosystem management and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Cliff sites are naturally protected by their inaccessibility against common disturbances, e.g., grazing or human activity [9]. They are known to harbour unique species diversity, including rare and endemic taxa [10][11][12][13][14]. Understanding how environmental damage scales with the number of climbing ascents is one of the central questions for sustainable management of the popular sport in semi-natural settings.…”
Section: Introductionmentioning
confidence: 99%
“…The scale and scope of the impacts our work has revealed has to be traded off against the social and economic benefits rock climbing brings to both climbers and rural communities. Recent authors have noted (DeCastro‐Arrazola et al, 2021) that, at broad spatial scales, the development of regional climbing management plans (e.g. National Park Service, 2002; North Carolina Department of Natural and Cultural Resources, 2019) is critical to ensuring the protection of areas of conservation concern and trading off the costs and benefits from development and access across landscapes.…”
Section: Discussionmentioning
confidence: 99%